2017
DOI: 10.1111/1753-0407.12607
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and alternative medicine in US adults with diabetes: Reasons for use and perceived benefits

Abstract: Although CAM may be a promising approach to improving health-related quality of life, future research should address efficacy and patient safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 30 publications
1
13
0
1
Order By: Relevance
“…A study in Australia reported a prevalence of 8%, but the study gathered data from patients about their visits to CAM practitioners only and did not include data on CAM use in general by patients with diabetes [44]. Other studies reporting the lowest prevalence of CAM use included studies in Libya (29%), Saudi Arabia (26%), USA (26%), Israel (23%) and Jordan (17%) [15,26,29,43,52]. Pooled prevalence of CAM use was 51% (95%CI 43%, 59%).…”
Section: Prevalence Of Cam Usementioning
confidence: 99%
“…A study in Australia reported a prevalence of 8%, but the study gathered data from patients about their visits to CAM practitioners only and did not include data on CAM use in general by patients with diabetes [44]. Other studies reporting the lowest prevalence of CAM use included studies in Libya (29%), Saudi Arabia (26%), USA (26%), Israel (23%) and Jordan (17%) [15,26,29,43,52]. Pooled prevalence of CAM use was 51% (95%CI 43%, 59%).…”
Section: Prevalence Of Cam Usementioning
confidence: 99%
“…More than 25% of older adults with diabetes used some type of CAM in the past year, which is only slightly less than the prevalence rate among the general adult population with diabetes (2). Older CAM users with diabetes utilized diverse types of CAM, and some of these CAM types had different prevalence rates by reason for use.…”
mentioning
confidence: 90%
“…Furthermore, patients should be educated to proactively discuss their CAM use with their health care providers, so that patient-centered care can be provided to meet the needs of older adults with diabetes. There are several limitations in this study, which are mentioned elsewhere (1,2). Despite the limitations, our findings highlight that CAM is widely used in older adults with diabetes.…”
mentioning
confidence: 98%
See 2 more Smart Citations